Implementing governance and regulation in Indonesia’s broadcasting industry - Badrul Redzuan Abu Hassan; Dewi Anggrayni; Roslina Abdul Latif; Putri Wahyuni (Penerbit Universiti Kebangsaan Malaysia, 2019)
An effective mechanism of governance and regulation is crucial to the well-being of a country’s media system. The idea of the State regulating the broadcasting industry does seem contradictory to economic liberalism and so surely, the State is wary that the industry operates in a free market economy for governance and regulation has its own repercussions. We situate our inquiry in the post-Reformation euphoria for media democratization in Indonesia, which historically, has established a strong relationship between oligarchic business interests and their political ambitions. Using focus group discussion as the primary method of elicitation, our research paper aims to understand deeper the strategic communicative process including meeting, planning, consultation and negotiation, and other implicit challenges involved in media governance and regulation process. We found that whilst the due process of governance and regulation remain real problem-solving events, they carry symbolic importance. There is still much improvement to be made in implementing regulatory framework including removing the ones that do not benefit the regulators. Our study implicates ethics and autonomy as two of the most outstanding issues in effective media co-regulation currently confronting the State and its regulating authorities in the face of ever-imposing media market deregulation on the broadcast industry. At the core of it all, the practice of media governance and regulation is essentially a series of ‘communicative event’ between the authorities, the State and the market.